Analisis Feminisme Dan Dekontruksi Citra Perempuan Pada Tokoh Hanum Dalam Novel Faith & The City - Nur Dina Camelia; Rozaiqah Noer Marisah; Siti Afiyana; Mas’odi Mas’odi (Student Scientific Creativity Journal, 2025)
Literature provides a wide scope of meaning for its readers, including in assessing the role of women as wives, which can be seen as good or bad depending on the author's point of view. In one of the hadiths narrated by Bukhari, women are described as having responsibility for the affairs of their husbands and children in the household. However, in the novel "Hanum and Rangga: Faith and The City," there is ambiguity regarding the views between the characters Rangga and Hanum regarding whether Hanum really meets the ideal criteria as a wife. This study aims to examine feminism and deconstruction of the image of women in the character Hanum. The method used is literature with a feminist and deconstruction approach. The results of the study reveal that Hanum is described as a wife who works without permission from her husband, setting aside her domestic role for her personal interests, while Rangga acts as a barrier to Hanum's dreams.